PEM Fuel Cells with Bio-Ethanol Processor Systems A Multidisciplinary Study of Modelling, Simulation, Fault Diagnosis and Advanced Control - Basualdo, Marta S.; Feroldi, Diego; Outbib, Rachid; SpringerLink (Online service) (London : Springer London, 2012)
An apparently appropriate control scheme for PEM fuel cells may actually lead to an inoperable plant when it is connected to other unit operations in a process with recycle streams and energy integration. PEM Fuel Cells with Bio-Ethanol Processor Systems presents a control system design that provides basic regulation of the hydrogen production process with PEM fuel cells. It then goes on to construct a fault diagnosis system to improve plant safety above this control structure. PEM Fuel Cells with Bio-Ethanol Processor Systems is divided into two parts: the first covers fuel cells and the second discusses plants for hydrogen production from bio-ethanol to feed PEM fuel cells. Both parts give detailed analyses of modeling, simulation, advanced control, and fault diagnosis. They give an extensive, in-depth discussion of the problems that can occur in fuel cell systems and propose a way to control these systems through advanced control algorithms. A significant part of the book is also given over to computer-aided engineering software tools that can be used to evaluate the dynamic performance of the overall plant. PEM Fuel Cells with Bio-Ethanol Processor Systems is intended for use by researchers and advanced students on chemical, electrical-electronic and mechanical engineering courses in which dynamics and control are incorporated with the traditional steady-state coverage of flowsheet synthesis, engineering economics and optimization.
1. Introduction -- 2. Description of PEM Fuel Cells System -- 3. Advanced Control Strategies for the Oxygen in the Cathode -- 4. Simulation and Control of PEMFCS Thermal Behavior -- 5. Fault Diagnosis of PEM Fuel Cell -- 6. Fault Diagnosis and Fault Tolerant Control of PEM Fuel Cell -- 7. Fuel Cell Hybrid Systems -- 8. Energy Management Strategies for Fuel Cell Hybrid Systems -- 9. Design and Control of an Integrated Bio-Ethanol Processor with PEMFC -- 10. Control Oriented Dynamic Model of the Bio-ethanol Processor System -- 11. Mathematical Model Implementation for Simulation Purposes -- 12. Plant-wide Control for Fuel Processor System with PEMFC -- 13. Fault Detectability Index for Optimal Monitoring System Design -- 14. Improved PCA Models for Fault Detection Using Delay Adjustment.
Keywords: Engineering; Chemistry; Chemical engineering; Computer simulation; System safety; Renewable energy sources; Biotechnology; Engineering; Renewable and Green Energy; Industrial Chemistry/Chemical Engineering; Electrochemistry; Environmental Engineering/Biotechnology.; Simulation and Modeling; Quality Control, Reliability, Safety and Risk